Coherences of charge migration increasing with molecular size: A case study for chloro-alkyne ions H(CC)_{n}Cl^{+} - Huihui Wang; Xue Ren; Xinran Ren; Liantuan Xiao; Suotang Jia; Yonggang Yang (Physical Review Research)
A key goal of ultrafast science is to pursue long-lived electronic coherences during molecular processes. The electronic coherence during charge migration can be characterized by the strength of the electronic flux. We report the size dependence of the de- and recoherences of charge migration in H(CC)_{n}Cl^{+} by systematic quantum dynamics simulations for n=1–4. The result is counterintuitive, namely the overall extent of electronic coherence increases with molecular size. Charge migration in the longest ions lasts for more than 100 fs, while it stops at about 10 fs in many previously investigated molecules.